Hepatoprotective and therapeutic effects of resveratrol: A focus on anti‐inflammatory and antioxidative activities. (17th January 2022) - Chupradit, Supat; Bokov, Dmitry; Zamanian, Mohammad Yassin; Heidari, Mahsa; Hakimizadeh, Elham
Abstract: Being the most essential organ in the body, the liver performs critical functions. Hepatic disorders, such as alcoholic liver disease, hepatic steatosis, liver fibrosis, nonalcoholic fatty liver disease, hepatocellular carcinoma, and hepatic failure, have an impact on the biochemical and physiological functions of the body. The main representative of the flavonoid subgroup of flavones, resveratrol (RES), exhibits suitable pharmacological activities for treating various liver diseases, such as fatty hepatitis, liver steatosis, liver cancer, and liver fibrosis. According to various studies, grapes and red wine are good sources of RES. RES has various health properties; it is anti‐inflammatory, anti‐apoptotic, antioxidative, and hepatoprotective against several hepatic diseases and hepatoxicity. Therefore, we performed a thorough research and created a summary of the distinct targets of RES in various stages of liver diseases. We concluded that RES inhibited liver inflammation essentially by causing a significant decrease in the expression of various pro‐inflammatory cytokines like TNF‐α, IL‐1α, IL‐1β, and IL‐6. It also inhibits the transcription factor nuclear NF‐κB that brings about the inflammatory cascade. RES also inhibits the PI3K/Akt/mTOR pathway to induce apoptosis. Additionally, it reduces oxidative stress in hepatic tissue by markedly reducing malondialdehyde (MDA) and nitric oxide (NO) contents and significantly increasing the levels of catalase (CAT), superoxide dismutase (SOD), and reduced hepatic glutathione (GSH), in addition to aspartate aminotransferase (AST) and alanine aminotransferase (ALT), against toxic chemicals like CC14, As2O3, and TTA. Due to its antioxidant, anti‐inflammatory, and anti‐fibrotic properties, RES reduces liver injury markers. RES is safe natural antioxidant that provides pharmacological rectification of the hepatoxicity of toxic chemicals.